Development of the acinus in the human lung. Issue 1 (January 1974) - Hislop, Alison; Reid, Lynne
Abstract : Hislop, Alison, and Reid, Lynne (1974). Thorax, 29, 90-94. Development of the acinus in the human lung. Development and remodelling of the acinus (those structures distal to the terminal bronchiolus) occurs during fetal life and childhood. Multiplication of the acinar air spaces and the structural changes they undergo have been described and represented schematically by summarizing previous studies, particularly those of the last two decades. Most acinar airways are present before birth. Future respiratory bronchioli are represented by the 19th intrauterine week; alveolar ducts are present as saccules by the 28th week. Alveolar sacs and alveoli, as properly described, do not appear until after birth: alveoli increase in number, particularly in the first seven or so years of life, and in size with thoracic growth.